Preparation method and application of antibacterial water inlet screen
By preparing an antibacterial water inlet barrier in the water inlet channel of the membrane element, the adsorption and bactericidal effect of the enhancer are used to solve the problem that bacteria are prone to breeding in the water inlet channel, extending the service life of the membrane element and improving the water purification efficiency.
Patent Information
- Application Number
- CN202410829421.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-25
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-06-25
AI Technical Summary
The current water inlet channels are prone to breeding bacteria and other microorganisms, affecting the service life of membrane components.
The antibacterial water inlet barrier is produced by adding reinforcement, antibacterial agent, antioxidant and base resin to the single screw extruder. The reinforcement is prepared from raw materials such as nitropyridine, hydrogen peroxide and hydrochloric acid through multiple steps, and has the dual effects of adsorption and bactericidal.
Effectively inhibit bacterial growth, extend the service life of membrane components, improve water purification flow, and reduce attenuation of membrane components' performance.
Smart Images

Figure BDA0004911401990000171 
Figure BDA0004911401990000181
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of antibacterial material preparation, and in particular to a preparation method and application of an antibacterial water inlet screen. Background Art
[0002] Reverse osmosis, nanofiltration and other filtration technologies are widely used in the water treatment industry. As the core component of the filtration system, membrane elements play a key role. Generally, membrane elements are composed of filter membranes, water inlet screens and water production channel cloths. The three together constitute the basic unit of the membrane page. The membrane pages of different layers are placed reasonably, sealed by adhesives, and rolled into membrane elements of a certain diameter with the water purification center tube as the center. When the membrane element is working, the raw water enters through the water inlet screen under a certain pressure, spirals forward, and part of it passes through the membrane and water production channel cloth into the water purification center tube to become clean water; part of it still passes through the water inlet screen layer to become concentrated water. Since the pore size of the reverse osmosis and nanofiltration membranes is very small, general microorganisms will be blocked on the side of the water inlet screen and the membrane, causing the space between the water inlet screen and the membrane to easily breed bacteria and other microorganisms, which has a significant adverse effect on the fouling of the membrane element and the clean water flow. Therefore, within the service life of the membrane element, the conventional operation is to flush it with acid and alkali solution, and the performance of the membrane element will be attenuated after flushing. When the membrane element is flushed a certain number of times or the technical indicators are not up to standard, it needs to be replaced in time. Although flushing can improve the contamination of the membrane element to a certain extent, it will also weaken the performance of the membrane element. At the same time, the flushing operation will bring additional material costs and time costs. Summary of the invention
[0003] The purpose of the present invention is to provide a method for preparing an antibacterial water inlet screen, which solves the problem that the water inlet channel is prone to breed bacteria and other microorganisms, thus affecting the service life of the membrane element.
[0004] The purpose of the present invention can be achieved through the following technical solutions:
[0005] A method for preparing an antibacterial water inlet screen specifically comprises the following steps:
[0006] Weigh 3-5 parts of a reinforcing agent, 0.1-5 parts of an antibacterial agent, 0.2-0.4 parts of an antioxidant and 100-120 parts of a base resin, add them into a single-screw extruder, and extrude them at a temperature of 170-230° C. to obtain an antibacterial water inlet screen.
[0007] The thickness of the antibacterial water inlet screen is 8-80mil, the angles of the warp and weft are 30-150°, and the density of the warp and weft is 5-50 per inch.
[0008] The antibacterial agent is one or two of silver, copper and zinc monomers mixed in any proportion, the antioxidant is one or two of antioxidant 1010 and antioxidant 168 mixed in any proportion, and the base resin is one or more of PP and PE mixed in any proportion.
[0009] Further, the reinforcing agent is prepared by the following steps:
[0010] Step A1: adding hydrochloric acid to a reaction kettle, stirring and adding nitropyridine and hydrogen peroxide solution at a speed of 60-80 r / min and a temperature of 15-20° C., reacting for 10-15 hours to obtain intermediate 1, mixing intermediate 1, triphenylphosphine and acetonitrile uniformly, reacting for 3-6 hours at a speed of 150-200 r / min and a temperature of 200-220° C., cooling to 20-25° C., filtering and removing the filtrate, and obtaining intermediate 2;
[0011] Step A2: uniformly mix intermediate 2, hydrochloric acid and ferrous chloride, react for 2-3 hours at a speed of 80-100 r / min and a temperature of 20-25° C. to obtain intermediate 3; uniformly mix intermediate 3, DCC, acrylic acid and DMF, react for 3-5 hours at a speed of 200-300 r / min and a temperature of 20-25° C. to obtain a modified monomer; uniformly mix dimethylaminoethyl methacrylate, bromodecane and acetonitrile, react for 10-12 hours at a speed of 80-120 r / min and a temperature of 45-60° C., cool to 20-25° C., filter and remove the filtrate to obtain a quaternary ammonium salt monomer;
[0012] Step A3: uniformly mix the modified monomer, quaternary ammonium salt monomer, γ-methacryloxypropyltrimethoxysilane, ethyl acrylate and DMF, stir and add potassium persulfate at a speed of 200-300 r / min and a temperature of 85-90° C., react for 6-8 hours to obtain a modifier, disperse the modifier in DMF, add a strengthening matrix and deionized water, react for 3-5 hours at a speed of 200-300 r / min and a temperature of 50-60° C. to obtain a strengthening agent.
[0013] Furthermore, the amount ratio of hydrochloric acid, nitropyridine and hydrogen peroxide solution in step A1 is 25mL:2.5g:30mL, the mass fraction of hydrochloric acid is 37%, the mass fraction of hydrogen peroxide solution is 10%, and the amount ratio of intermediate 1, triphenylphosphine and acetonitrile is 1g:2.16g:30mL.
[0014] Furthermore, in step A2, the usage ratio of intermediate 2, hydrochloric acid and ferrous chloride is 1g:20mL:1g, the mass fraction of hydrochloric acid is 10%, the usage ratio of intermediate 3, DCC and acrylic acid is 1g:0.67g:9.71mL, and the usage ratio of dimethylaminoethyl methacrylate, bromodecane and acetonitrile is 1g:1.4g:12.23mL.
[0015] Further, the amount ratio of the modified monomer, quaternary ammonium salt monomer, γ-methacryloxypropyltrimethoxysilane and ethyl acrylate described in step A3 is 1g:0.57g:10mL:20mL, the amount of potassium persulfate is 0.1-0.3% of the total mass of the modified monomer, quaternary ammonium salt monomer, γ-methacryloxypropyltrimethoxysilane and ethyl acrylate, and the amount ratio of the modifier, the strengthening matrix and the deionized water is 4g:1g:20mL.
[0016] Further, the strengthening matrix is made by the following steps:
[0017] Step B1: CTAB solution, HAuCl4 solution and NaBH4 solution are mixed evenly, and reacted at a speed of 100-150 r / min and a temperature of 25-30° C. for 0.5-1 h to obtain a seed solution;
[0018] Step B2: Evenly mix the CTAB solution, AgNO3 solution, HAuC l4 solution and L-ascorbic acid solution to obtain a seed growth solution, evenly mix the seed solution and the seed growth solution, and let stand for 10-12 hours to obtain thorn-shaped AuNR nanoparticles;
[0019] Step B3: Disperse the thorny AuNR nanoparticles into deionized water, stir for 10-15 min at a rotation speed of 6500-7000 r / min, then add TiF4 solution and mesoporous silica to the solution and stir for 30-50 min, and obtain a reinforced matrix at a temperature of 100-120°C and a pressure of 25-30 MPa.
[0020] Furthermore, the dosage ratio of the CTAB solution, HAuC l4 solution and NaBH4 solution in step B1 is 1 mL:1 mL:0.12 mL, the concentration of the CTAB solution is 0.2 mol / L, the concentration of the HAuC l4 solution is 0.5 mol / L, and the concentration of the NaBH4 solution is 0.01 mol / L.
[0021] Furthermore, the dosage ratio of the CTAB solution, AgNO3 solution, HAuC14 solution and L-ascorbic acid solution in step B2 is 95 mL:10 mL:5 mL:0.55 mL, the concentration of the CTAB solution is 0.1 mol / L, the concentration of the AgNO3 solution is 0.01 mol / L, the concentration of the HAuC14 solution is 0.01 mol / L, and the concentration of the L-ascorbic acid solution is 0.1 mol / L.
[0022] Furthermore, in step B3, the dosage ratio of deionized water, TiF4 solution, thorny AuNR nanoparticles and mesoporous silica is 60 mL: 30 mL: 1 g: 5 g, and the concentration of TiF4 solution is 0.25 mol / L.
[0023] Beneficial effects of the present invention: The present invention adds a reinforcing agent, an antibacterial agent, an antioxidant and a base resin to a single screw extruder, and extrudes and molds to prepare an antibacterial water inlet screen. The reinforcing agent is chlorinated with nitropyridine, hydrogen peroxide and hydrochloric acid as raw materials to prepare intermediate 1, and intermediate 1 is reacted with triphenylphosphine so that the chlorine atom site on intermediate 1 and the phosphorus atom site on triphenylphosphine undergo Wittig reaction to produce a quaternary phosphonium salt structure to prepare intermediate 2, and intermediate 2 is subjected to Bechamp reduction reaction so that the nitro group on intermediate 2 is converted into an amino group to prepare intermediate 3, and intermediate 3 and acrylic acid are reacted under the action of DCC so that the amino group on intermediate 3 and the carboxyl group on acrylic acid undergo dehydration condensation to prepare a modified monomer, and the modified monomer, quaternary ammonium salt monomer, and γ-methacryloyloxy are reacted. The invention discloses a method for preparing a reinforcing agent by mixing propyltrimethoxysilane and ethyl acrylate and preparing a modifier under the action of potassium persulfate, dispersing the modifier in DMF, adding a reinforcing matrix and deionized water, and performing surface modification by a silane coupling agent. The modified monomer enables the organic modifier to be chemically combined with the inorganic reinforcing matrix, and the silane coupling agent can increase the bonding force between the reinforcing agent and the base resin so that the reinforcing agent is not easy to separate out from the base resin. The reinforcing matrix is obtained by dispersing thorn-shaped AuNR nanoparticles into SiO2 / TiO2 composite materials, wherein the thorn-shaped AuNR nanoparticles are prepared by a seed growth method. The reinforcing agent of the invention is composed of two parts, an organic molecule and an inorganic molecule. The organic part, quaternary phosphonium salt and quaternary ammonium salt, both have the ability to adsorb negatively charged bacteria. At the same time, the long-chain hydrophobic group of the quaternary ammonium salt can also be inserted into the lipid layer of the bacteria, changing the permeability of the cell membrane, destroying the membrane structure, inhibiting the activity of enzymes or proteins, and affecting the cell metabolic process. The quaternary phosphonium group increases the stability of the quaternary ammonium salt. The inorganic part, titanium dioxide, can destroy the cell membrane and cell wall of bacteria and kill them. The composite of mesoporous silica and titanium dioxide carries a large number of thorny AuNR particles, which can pierce the cell membrane of bacteria while adsorbing them, greatly improving the efficiency of sterilization. DETAILED DESCRIPTION
[0024] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] Example 1
[0026] A method for preparing an antibacterial water inlet screen specifically comprises the following steps:
[0027] Weigh 3 parts of a reinforcing agent, 0.1 parts of a silver monomer, 0.1 parts of an antioxidant 168 and 100 parts of a PP resin, add them into a single-screw extruder, and extrude them at a temperature of 170° C. to obtain an antibacterial water inlet screen.
[0028] The PP resin is of extrusion grade, with a melt index of 1 g / 10 min, 230C / 2.16 kg.
[0029] The reinforcing agent is prepared by the following steps:
[0030] Step A1: adding hydrochloric acid to a reaction kettle, stirring and adding nitropyridine and hydrogen peroxide solution at a speed of 60 r / min and a temperature of 15° C., reacting for 10 hours to obtain intermediate 1, mixing intermediate 1, phenylphosphine and acetonitrile uniformly, reacting for 3 hours at a speed of 150 r / min and a temperature of 200° C., cooling to 20° C., filtering and removing the filtrate, and obtaining intermediate 2;
[0031] Step A2: uniformly mix intermediate 2, hydrochloric acid and ferrous chloride, react at a speed of 80 r / min and a temperature of 20° C. for 2 h to obtain intermediate 3; uniformly mix intermediate 3, DCC, acrylic acid and DMF, react at a speed of 200 r / min and a temperature of 20° C. for 3 h to obtain a modified monomer; uniformly mix dimethylaminoethyl methacrylate, bromodecane and acetonitrile, react at a speed of 80 r / min and a temperature of 45° C. for 10 h, cool to 20° C., filter and remove the filtrate to obtain a quaternary ammonium salt monomer;
[0032] Step A3: uniformly mix the modified monomer, quaternary ammonium salt monomer, γ-methacryloxypropyltrimethoxysilane, ethyl acrylate and DMF, stir and add potassium persulfate at a speed of 200 r / min and a temperature of 85° C., react for 6 hours to obtain a modifier, disperse the modifier in DMF, add a strengthening matrix and deionized water, react for 3 hours at a speed of 200 r / min and a temperature of 50° C., and obtain a strengthening agent.
[0033] The amount ratio of hydrochloric acid, nitropyridine and hydrogen peroxide solution described in step A1 is 25mL:2.5g:30mL, the mass fraction of hydrochloric acid is 37%, the mass fraction of hydrogen peroxide solution is 10%, the amount ratio of intermediate 1, triphenylphosphine and acetonitrile is 1g:2.16g:30mL, the amount of hydrochloric acid is 500mL, and the amount of intermediate 1 is 50g.
[0034] In step A2, the amount ratio of intermediate 2, hydrochloric acid and ferrous chloride is 1g:20mL:1g, the mass fraction of hydrochloric acid is 10%, the amount ratio of intermediate 3, DCC and acrylic acid is 1g:0.67g:9.71mL, the amount ratio of dimethylaminoethyl methacrylate, bromodecane and acetonitrile is 1g:1.4g:12.23mL, the amount of intermediate 2 is 100g, the amount of intermediate 3 is 187g, and the amount of dimethylethyl methacrylate is 157g.
[0035] The amount ratio of the modified monomer, quaternary ammonium salt monomer, γ-methacryloxypropyltrimethoxysilane and ethyl acrylate described in step A3 is 1g:0.57g:10mL:20mL, the amount of potassium persulfate is 0.1-0.3% of the total mass of the modified monomer, quaternary ammonium salt monomer, γ-methacryloxypropyltrimethoxysilane and ethyl acrylate, the amount ratio of the modifier, the strengthening matrix and deionized water is 4g:1g:20mL, the amount of the modified monomer is 86g, and the amount of the modifier is 150g.
[0036] The reinforced matrix is made by the following steps:
[0037] Step B1: CTAB solution, HAuCl4 solution and NaBH4 solution were mixed evenly, and reacted at a speed of 100 r / min and a temperature of 25° C. for 0.5 h to obtain a seed solution;
[0038] Step B2: Evenly mix the CTAB solution, AgNO3 solution, HAuC l4 solution and L-ascorbic acid solution to obtain a seed growth solution, evenly mix the seed solution and the seed growth solution, and let stand for 10 hours to obtain thorn-shaped AuNR nanoparticles;
[0039] Step B3: The thorny AuNR nanoparticles were dispersed in deionized water, stirred at a speed of 6500 r / min for 10 min, and then TiF4 solution and mesoporous silica were added to the solution and stirred for 30 min. A reinforced matrix was obtained at a temperature of 100°C and a pressure of 25 MPa.
[0040] The dosage ratio of the CTAB solution, HAuC l4 solution and NaBH4 solution in step B1 is 1 mL: 1 mL: 0.12 mL, the concentration of the CTAB solution is 0.2 mol / L, the concentration of the HAuC l4 solution is 0.5 mol / L, the concentration of the NaBH4 solution is 0.01 mol / L, and the dosage of the CTAB solution is 200 mL.
[0041] The dosage ratio of the CTAB solution, AgNO3 solution, HAuCl4 solution and L-ascorbic acid solution in step B2 is 95mL:10mL:5mL:0.55mL, the concentration of the CTAB solution is 0.1mol / L, the concentration of the AgNO3 solution is 0.01mol / L, the concentration of the HAuCl4 solution is 0.01mol / L, and the concentration of the L-ascorbic acid solution is 0.1mol / L. The dosage of the CTAB solution is 2000mL.
[0042] In step B3, the dosage ratio of deionized water, TiF4 solution, thorny AuNR nanoparticles and mesoporous silica is 60mL:30mL:1g:5g, the concentration of TiF4 solution is 0.25mol / L, and the dosage of deionized water is 2000mL.
[0043] Example 2
[0044] A method for preparing an antibacterial water inlet screen specifically comprises the following steps:
[0045] 5 parts of a reinforcing agent, 0.2 parts of a copper monomer, 0.2 parts of an antioxidant 168 and 120 parts of a PP resin were weighed, added into a single-screw extruder, and extruded at a temperature of 230° C. to obtain an antibacterial water inlet screen.
[0046] The PP resin is of extrusion grade, with a melt index of 5 g / 10 min, 230C / 2.16 kg.
[0047] The reinforcing agent is prepared by the following steps:
[0048] Step A1: adding hydrochloric acid to a reaction kettle, stirring and adding nitropyridine and hydrogen peroxide solution at a speed of 80 r / min and a temperature of 20° C., reacting for 15 hours to obtain intermediate 1, mixing intermediate 1, triphenylphosphine and acetonitrile uniformly, reacting for 6 hours at a speed of 200 r / min and a temperature of 220° C., cooling to 25° C., filtering and removing the filtrate, and obtaining intermediate 2;
[0049] Step A2: The intermediate 2, 475 mL of hydrochloric acid and ferrous chloride are mixed uniformly, and the mixture is reacted at a speed of 100 r / min and a temperature of 25° C. for 3 h to obtain the intermediate 3; the intermediate 3, DCC, acrylic acid and DMF are mixed uniformly, and the mixture is reacted at a speed of 300 r / min and a temperature of 25° C. for 5 h to obtain the modified monomer; dimethylaminoethyl methacrylate, bromodecane and acetonitrile are mixed uniformly, and the mixture is reacted at a speed of 120 r / min and a temperature of 60° C. for 12 h, and then the mixture is cooled to 25° C., and the filtrate is filtered to obtain the quaternary ammonium salt monomer;
[0050] Step A3: uniformly mix the modified monomer, quaternary ammonium salt monomer, γ-methacryloxypropyltrimethoxysilane, ethyl acrylate and DMF, stir and add potassium persulfate at a speed of 300 r / min and a temperature of 90° C., react for 8 hours to obtain a modifier, disperse the modifier in DMF, add a strengthening matrix and deionized water, react for 5 hours at a speed of 300 r / min and a temperature of 60° C., and obtain a strengthening agent.
[0051] The amount ratio of hydrochloric acid, nitropyridine and hydrogen peroxide solution described in step A1 is 25mL:2.5g:30mL, the mass fraction of hydrochloric acid is 37%, the mass fraction of hydrogen peroxide solution is 10%, the amount ratio of intermediate 1, triphenylphosphine and acetonitrile is 1g:2.16g:30mL, the amount of hydrochloric acid is 500mL, and the amount of intermediate 1 is 50g.
[0052] In step A2, the amount ratio of intermediate 2, hydrochloric acid and ferrous chloride is 1g:20mL:1g, the mass fraction of hydrochloric acid is 10%, the amount ratio of intermediate 3, DCC and acrylic acid is 1g:0.67g:9.71mL, the amount ratio of dimethylaminoethyl methacrylate, bromodecane and acetonitrile is 1g:1.4g:12.23mL, the amount of intermediate 2 is 100g, the amount of intermediate 3 is 187g, and the amount of dimethylethyl methacrylate is 157g.
[0053] The amount ratio of the modified monomer, quaternary ammonium salt monomer, γ-methacryloxypropyltrimethoxysilane and ethyl acrylate described in step A3 is 1g:0.57g:10mL:20mL, the amount of potassium persulfate is 0.1-0.3% of the total mass of the modified monomer, quaternary ammonium salt monomer, γ-methacryloxypropyltrimethoxysilane and ethyl acrylate, the amount ratio of the modifier, the strengthening matrix and deionized water is 4g:1g:20mL, the amount of the modified monomer is 86g, and the amount of the modifier is 150g.
[0054] The reinforced matrix is made by the following steps:
[0055] Step B1: CTAB solution, HAuCl4 solution and NaBH4 solution were mixed evenly, and reacted at a speed of 100 r / min and a temperature of 25° C. for 0.5 h to obtain a seed solution;
[0056] Step B2: Evenly mix the CTAB solution, AgNO3 solution, HAuC l4 solution and L-ascorbic acid solution to obtain a seed growth solution, evenly mix the seed solution and the seed growth solution, and let stand for 10 hours to obtain thorn-shaped AuNR nanoparticles;
[0057] Step B3: The thorny AuNR nanoparticles were dispersed in deionized water, stirred at a speed of 6500 r / min for 10 min, and then TiF4 solution and mesoporous silica were added to the solution and stirred for 30 min. A reinforced matrix was obtained at a temperature of 100°C and a pressure of 25 MPa.
[0058] The dosage ratio of the CTAB solution, HAuC l4 solution and NaBH4 solution in step B1 is 1 mL: 1 mL: 0.12 mL, the concentration of the CTAB solution is 0.2 mol / L, the concentration of the HAuC l4 solution is 0.5 mol / L, the concentration of the NaBH4 solution is 0.01 mol / L, and the dosage of the CTAB solution is 200 mL.
[0059] The dosage ratio of the CTAB solution, AgNO3 solution, HAuCl4 solution and L-ascorbic acid solution in step B2 is 95mL:10mL:5mL:0.55mL, the concentration of the CTAB solution is 0.1mol / L, the concentration of the AgNO3 solution is 0.01mol / L, the concentration of the HAuCl4 solution is 0.01mol / L, and the concentration of the L-ascorbic acid solution is 0.1mol / L. The dosage of the CTAB solution is 2000mL.
[0060] In step B3, the dosage ratio of deionized water, TiF4 solution, thorny AuNR nanoparticles and mesoporous silica is 60mL:30mL:1g:5g, the concentration of TiF4 solution is 0.25mol / L, and the dosage of deionized water is 2000mL.
[0061] Example 3
[0062] A method for preparing an antibacterial water inlet screen specifically comprises the following steps:
[0063] 4 parts of a reinforcing agent, 0.15 parts of a zinc monomer, 0.15 parts of an antioxidant 1010 and 110 parts of a PE resin were weighed, added into a single screw extruder, and extruded at a temperature of 200° C. to obtain an antibacterial water inlet screen.
[0064] The PE resin is of extrusion grade, with a melt index of 1 g / 10 min, 190C / 2.16 kg.
[0065] The reinforcing agent is prepared by the following steps:
[0066] Step A1: adding hydrochloric acid to a reaction kettle, stirring and adding nitropyridine and hydrogen peroxide solution at a speed of 70 r / min and a temperature of 18° C., reacting for 12 hours to obtain intermediate 1, mixing intermediate 1, triphenylphosphine and acetonitrile, reacting for 5 hours at a speed of 180 r / min and a temperature of 210° C., cooling to 22° C., filtering and removing the filtrate, and obtaining intermediate 2;
[0067] Step A2: Intermediate 2, hydrochloric acid and ferrous chloride are mixed uniformly, and reacted at a speed of 90 r / min and a temperature of 22° C. for 2.5 hours to obtain intermediate 3; intermediate 3, DCC, acrylic acid and DMF are mixed uniformly, and reacted at a speed of 260 r / min and a temperature of 22° C. for 4 hours to obtain a modified monomer; dimethylaminoethyl methacrylate, bromodecane and acetonitrile are mixed uniformly, and reacted at a speed of 100 r / min and a temperature of 52° C. for 11 hours, and then cooled to 22° C., and the filtrate is filtered to obtain a quaternary ammonium salt monomer;
[0068] Step A3: uniformly mix the modified monomer, quaternary ammonium salt monomer, γ-methacryloxypropyltrimethoxysilane, ethyl acrylate and DMF, stir and add potassium persulfate at a speed of 260 r / min and a temperature of 88°C, and react for 7 hours to obtain a modifier, disperse the modifier in DMF, add a strengthening matrix and deionized water, and react for 4 hours at a speed of 260 r / min and a temperature of 55°C to obtain a strengthening agent.
[0069] The amount ratio of hydrochloric acid, nitropyridine and hydrogen peroxide solution described in step A1 is 25mL:2.5g:30mL, the mass fraction of hydrochloric acid is 37%, the mass fraction of hydrogen peroxide solution is 10%, the amount ratio of intermediate 1, triphenylphosphine and acetonitrile is 1g:2.16g:30mL, the amount of hydrochloric acid is 500mL, and the amount of intermediate 1 is 50g.
[0070] In step A2, the amount ratio of intermediate 2, hydrochloric acid and ferrous chloride is 1g:20mL:1g, the mass fraction of hydrochloric acid is 10%, the amount ratio of intermediate 3, DCC and acrylic acid is 1g:0.67g:9.71mL, the amount ratio of dimethylaminoethyl methacrylate, bromodecane and acetonitrile is 1g:1.4g:12.23mL, the amount of intermediate 2 is 100g, the amount of intermediate 3 is 187g, and the amount of dimethylethyl methacrylate is 157g.
[0071] The amount ratio of the modified monomer, quaternary ammonium salt monomer, γ-methacryloxypropyltrimethoxysilane and ethyl acrylate described in step A3 is 1g:0.57g:10mL:20mL, the amount of potassium persulfate is 0.1-0.3% of the total mass of the modified monomer, quaternary ammonium salt monomer, γ-methacryloxypropyltrimethoxysilane and ethyl acrylate, the amount ratio of the modifier, the strengthening matrix and deionized water is 4g:1g:20mL, the amount of the modified monomer is 86g, and the amount of the modifier is 150g.
[0072] The reinforced matrix is made by the following steps:
[0073] Step B1: CTAB solution, HAuCl4 solution and NaBH4 solution were mixed evenly, and reacted at a speed of 100 r / min and a temperature of 25° C. for 0.5 h to obtain a seed solution;
[0074] Step B2: Evenly mix the CTAB solution, AgNO3 solution, HAuC l4 solution and L-ascorbic acid solution to obtain a seed growth solution, evenly mix the seed solution and the seed growth solution, and let stand for 10 hours to obtain thorn-shaped AuNR nanoparticles;
[0075] Step B3: Disperse 1.2 g of thorny AuNR nanoparticles into deionized water, stir for 10 min at a rotation speed of 6500 r / min, then add TiF4 solution and mesoporous silica to the solution and stir for 30 min. At a temperature of 100°C and a pressure of 25 MPa, a reinforced matrix is obtained.
[0076] The dosage ratio of the CTAB solution, HAuC l4 solution and NaBH4 solution in step B1 is 1 mL: 1 mL: 0.12 mL, the concentration of the CTAB solution is 0.2 mol / L, the concentration of the HAuC l4 solution is 0.5 mol / L, the concentration of the NaBH4 solution is 0.01 mol / L, and the dosage of the CTAB solution is 200 mL.
[0077] The dosage ratio of the CTAB solution, AgNO3 solution, HAuCl4 solution and L-ascorbic acid solution in step B2 is 95mL:10mL:5mL:0.55mL, the concentration of the CTAB solution is 0.1mol / L, the concentration of the AgNO3 solution is 0.01mol / L, the concentration of the HAuCl4 solution is 0.01mol / L, and the concentration of the L-ascorbic acid solution is 0.1mol / L. The dosage of the CTAB solution is 2000mL.
[0078] In step B3, the dosage ratio of deionized water, TiF4 solution, thorny AuNR nanoparticles and mesoporous silica is 60 mL: 30 mL: 1 g: 5 g, the concentration of TiF4 solution is 0.25 mol / L, and the dosage of deionized water is 2000 mL.
[0079] Comparative Example 1
[0080] A method for preparing an antibacterial water inlet screen specifically comprises the following steps:
[0081] Weigh 0.1 parts of metallic silver, 0.1 parts of antioxidant 168, 0.1 parts of antioxidant 1010 and 100 parts of PP resin, add them into a single-screw extruder, and extrude them at a temperature of 170° C. to obtain an antibacterial water inlet screen.
[0082] The PP resin is of extrusion grade, with a melt index of 1 g / 10 min, 230C / 2.16 kg.
[0083] Comparative Example 2
[0084] A method for preparing an antibacterial water inlet screen specifically comprises the following steps:
[0085] Weigh 5 parts of metallic copper, 0.2 parts of antioxidant 168, 0.2 parts of antioxidant 1010 and 120 parts of PP resin, add them into a single-screw extruder, and extrude them at a temperature of 230° C. to obtain an antibacterial water inlet screen.
[0086] The PP resin is of extrusion grade, with a melt index of 1 g / 10 min, 230C / 2.16 kg.
[0087] Comparative Example 3
[0088] A method for preparing an antibacterial water inlet screen specifically comprises the following steps:
[0089] Weigh 1 part of metallic silver, 1 part of metallic copper, 0.15 parts of antioxidant 168, 0.15 parts of antioxidant 1010 and 110 parts of PP resin, add into a single screw extruder, and extrude and mold them at a temperature of 200° C. to obtain an antibacterial water inlet screen.
[0090] The PP resin is of extrusion grade, with a melt index of 1 g / 10 min, 230C / 2.16 kg.
[0091] Comparative Example 4
[0092] A method for preparing an antibacterial water inlet screen specifically comprises the following steps:
[0093] Weigh 0.1 parts of metallic copper, 0.1 parts of antioxidant 168, 0.1 parts of antioxidant 1010 and 100 parts of PE resin, add them into a single-screw extruder, and extrude them at a temperature of 170° C. to obtain an antibacterial water inlet screen.
[0094] The PP resin is of extrusion grade, with a melt index of 1 g / 10 min, 230C / 2.16 kg.
[0095] Comparative Example 5
[0096] A method for preparing an antibacterial water inlet screen specifically comprises the following steps:
[0097] Weigh 5 parts of metallic zinc, 0.2 parts of antioxidant 168, 0.2 parts of antioxidant 1010 and 120 parts of PE resin, add them into a single-screw extruder, and extrude them at a temperature of 230° C. to obtain an antibacterial water inlet screen.
[0098] The PP resin is of extrusion grade, with a melt index of 1 g / 10 min, 230C / 2.16 kg.
[0099] Comparative Example 6
[0100] A method for preparing an antibacterial water inlet screen specifically comprises the following steps:
[0101] Weigh 1 part of metallic copper, 1 part of metallic zinc, 0.15 parts of antioxidant 168, 0.15 parts of antioxidant 1010 and 110 parts of PE resin, add into a single screw extruder, and extrude and mold at a temperature of 200° C. to obtain an antibacterial water inlet screen.
[0102] The PP resin is of extrusion grade, with a melt index of 1 g / 10 min, 230C / 2.16 kg.
[0103] Comparative Example 7
[0104] A method for preparing an antibacterial water inlet screen specifically comprises the following steps:
[0105] Weigh 0.1 parts of metallic silver, 0.1 parts of antioxidant 168, 0.1 parts of antioxidant 1010 and 100 parts of PP resin, add them into a single-screw extruder, and extrude them at a temperature of 170° C. to obtain an antibacterial water inlet screen.
[0106] The PP resin is of extrusion grade, with a melt index of 1 g / 10 min, 230C / 2.16 kg.
[0107] Comparative Example 8
[0108] A method for preparing an antibacterial water inlet screen specifically comprises the following steps:
[0109] Weigh 5 parts of metallic zinc, 0.2 parts of antioxidant 168, 0.2 parts of antioxidant 1010 and 120 parts of PP resin, add them into a single-screw extruder, and extrude them at a temperature of 230° C. to obtain an antibacterial water inlet screen.
[0110] The PP resin is of extrusion grade, with a melt index of 1 g / 10 min, 230C / 2.16 kg.
[0111] Comparative Example 9
[0112] A method for preparing an antibacterial water inlet screen specifically comprises the following steps:
[0113] Weigh 1 part of metallic silver, 1 part of metallic zinc, 0.15 parts of antioxidant 168, 0.15 parts of antioxidant 1010 and 110 parts of PP resin, add into a single screw extruder, and extrude and mold at a temperature of 200° C. to obtain an antibacterial water inlet screen.
[0114] The PP resin is of extrusion grade, with a melt index of 1 g / 10 min, 230C / 2.16 kg.
[0115] Comparative Example 10
[0116] Compared with Example 1, this comparative example uses a modifier instead of a reinforcing agent, and the remaining steps are the same.
[0117] Comparative Example 11
[0118] Compared with Example 1, this comparative example uses a modified matrix instead of a reinforcing agent, and the remaining steps are the same.
[0119] Comparative Example 12
[0120] Compared with Example 1, this comparative example uses a modified monomer instead of a modifying agent, and the remaining steps are the same.
[0121] The antibacterial water inlet screens prepared in Examples 1-3 and Comparative Examples 1-12 were tested for their sterilization capabilities at 12h and 24h according to the standard of GB / T31402-2015. The results are shown in the following table:
[0122]
[0123]
[0124] It can be seen from the above table that the bactericidal effect of the antibacterial water inlet screens prepared in Examples 1-3 in 12 hours is close to the bactericidal effect of silver ions in 24 hours, and the bactericidal speed is faster than that of silver ions. At 24 hours, the bactericidal capacity of the antibacterial water inlet screens prepared in Examples 1-3 reached more than 99%, and the bactericidal effect was better than that of silver ions. The bactericidal effect of Comparative Examples 10-12 was between copper ions and silver ions, which was far worse than that of Examples 1-3. This shows that the antibacterial water inlet screens prepared by the enhancer of the present invention have a fast and excellent bactericidal effect.
[0125] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
Claims
1. A method for preparing an antibacterial water inlet screen, characterized in that : Specifically include the following steps: Weigh 0.1-5 parts of a reinforcing agent, 0.1-5 parts of an antibacterial agent, 0.2-0.4 parts of an antioxidant and 100-120 parts of a base resin, add them into a single-screw extruder, and extrude and shape them to obtain an antibacterial water inlet screen; The reinforcing agent is prepared by the following steps: Step A1: hydrochloric acid was added to a reaction vessel, stirred and nitropyridine and hydrogen peroxide solution were added to react to obtain intermediate 1, the intermediate 1, triphenylphosphine, acetonitrile was mixed and reacted, and the filtrate was removed by filtration to obtain intermediate 2; Step A2: reacting intermediate 2, hydrochloric acid and ferrous chloride to obtain intermediate 3, reacting intermediate 3, DCC, acrylic acid and DMF to obtain a modified monomer, reacting dimethylaminoethyl methacrylate, decane bromide and acetonitrile to obtain a quaternary ammonium salt monomer by filtering and removing the filtrate; Step A3: mixing a modified monomer, a quaternary ammonium salt monomer, γ-methacryloxypropyltrimethoxysilane, ethyl acrylate and DMF, adding potassium persulfate, reacting to obtain a modifier, dispersing the modifier in DMF, adding a strengthening matrix and deionized water to mix and react, and obtaining a strengthening agent; The amount ratio of hydrochloric acid, nitropyridine and hydrogen peroxide solution in step A1 is 25mL:2.5g:30mL, and the amount ratio of intermediate 1, triphenylphosphine and acetonitrile is 1g:2.16g:30mL; In step A2, the ratio of intermediate 2, hydrochloric acid and ferrous chloride is 1 g: 20 mL: 1 g, the ratio of intermediate 3, DCC and acrylic acid is 1 g: 0.67 g: 9.71 mL, and the ratio of dimethylaminoethyl methacrylate, bromodecane and acetonitrile is 1 g: 1.4 g: 12.23 mL; The modified monomer, quaternary ammonium salt monomer, γ-methacryloxypropyltrimethoxysilane and ethyl acrylate described in step A3 are used in a ratio of 1g:0.57g:10mL:20mL, the amount of potassium persulfate is 0.1-0.3% of the total mass of the modified monomer, quaternary ammonium salt monomer, γ-methacryloxypropyltrimethoxysilane and ethyl acrylate, and the amount of the modifier, the strengthening matrix and the deionized water is used in a ratio of 4g:1g:20mL; The reinforced matrix is made by the following steps: Step B1: uniformly mixing the CTAB solution, HAuCl4 solution and NaBH4 solution to prepare a seed solution; Step B2: uniformly mixing the CTAB solution, the AgNO3 solution, the HAuCl4 solution and the L-ascorbic acid solution to obtain a seed growth solution, mixing the seed solution and the seed growth solution, and standing to obtain thorn-shaped AuNR nanoparticles; Step B3: dispersing the thorn-shaped AuNR nanoparticles into deionized water, adding TiF4 solution and mesoporous silica, and reacting to obtain a reinforced matrix; The antibacterial agent is one or two of silver, copper and zinc monomers mixed in any proportion, the antioxidant is one or two of antioxidant 1010 and antioxidant 168 mixed in any proportion, and the base resin is one or more of PP and PE mixed in any proportion; The dosage ratio of the CTAB solution, HAuCl4 solution and NaBH4 solution in step B1 is 1 mL:1 mL:0.12 mL; The dosage ratio of the CTAB solution, AgNO3 solution, HAuCl4 solution and L-ascorbic acid solution in step B2 is 95 mL: 10 mL: 5 mL: 0.55 mL; The amount ratio of deionized water, TiF4 solution, thorny AuNR nanoparticles and mesoporous silica in step B3 is 60mL:30mL:1g:5g.
2. Application of the antibacterial water inlet screen prepared by the preparation method according to claim 1, wherein the application is in the field of liquid filtration water inlet screens.
Citation Information
Patent Citations
Nano-antibacterial water treatment material and preparation method thereof
CN105131393A
Ultrafiltration polyethylene porous membrane for water treatment and preparation process thereof
CN112755789A